O tendenciâh i perspektivah razvitiâ rossijskogo zakonodatel'stva o pogrebenii i nohoronnom dele - Barkov, Aleksej Vladimirovič; Graâčev, Roman Ûr'evič (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
This article examines the tendencies and prospects of development of Russian legislation on the burial and funeral business. Identifying the advantages and disadvantages of two actively discussed in Russia of the draft laws «On introducing amendments and addenda to the Federal law «On burial and funeral business» prepared by the Federal Antimonopoly service and the funeral community (focused on the self-regulation of the funeral industry), and «About the funeral business», published by the Ministry of construction in the fall of 2014 (aimed at the domination of the license regulation of the market of ritual services), the authors conclude about the necessity of combining the advan-tages of two models: self-regulation and licensing. As perspective directions of improvement of the legislation on the burial and funeral business is justified the possibility of using ideology of social entrepreneurship, received practical application in developed legal systems
Keywords: firmy pogrzebowe; koncesja; samoregulacja; przedsiębiorczość społeczna